Penanaman Karakter Kesantunan Bahasa Pada Siswa MTs. Bahrul Ulum Desa Bulu Kecamatan Balen Kabupaten Bojonegoro - Abdul Ghoni Asror; Ali Mujahidin; Heru Ismaya; Ali Noeruddin; Joko Setiyono (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2018)
The crucial problem we face in MTs Bahrul Ulum is on student character and their linguistic. They did not know how did their language which they use to communicate with the teacher is polite or not. This will impact to their character in a large community. Because language is the great factor to the successful character building. Based on our opinion, there must be a great attention to the student language in MTs Bahrul Ulum. The used method in this service is giving the counseling with many variant games, and it make the interesting session to the student. This Dedication activities consist of three steps: Pre service, service, and post service. The impact in this post service for teacher and their student is to analyses how far the dedication effect to increase the character building and good language due to the students.